Epidemiología de incidentes viales Medellín-Colombia, 2010-2015 (2017)
ABSTRACT: Road traffic incidents (rti) transfer kinetic energy between inert and living surfaces on roads. They cause fatal and non-fatal injuries, affecting people's health, well-being and productivity. They are not random, and they are not accidents like the United Nations pointed out many decades ago. Objective: the purpose of this study is to describe RTA epidemiology in Medellin from 2010 to 2015 as a referent and propose a road traffic management model- a rtmm. Methodology: this is a retrospective study using different rti sources and a univariate or bivariate analysis. Results: from 2010 to 2015, there was an increasing rti record of 275,000 events, with a mean of 45,000/ year and 135/day, and what has not been recorded could be 4 times more. There were injuries in 50% of the rti recorded in police traffic accident reports (ptar), with a mean of 300 casualties/year an approximately 3,000 injured/ year. However, the non-recorded injured could be ten times more, 30,000/year. Most rtis affect the poor, pedestrians, motorcyclists and cyclists mainly males of ages 15 to 29 in residential areas. Conclusions: leadership, government policies, a Road Traffic Safety Observatory and Safe Mobility Plan Management up to 2020 are critical to decrease rti risk, exposure and frequency.